Risk Assessment of Neonatal Exposure to Low Frequency Noise Based on Balance in Mice - Ohgami, Nobutaka; Oshino, Reina; Ninomiya, Hiromasa; Li, Xiang; Kato, Masashi; Yajima, Ichiro; Kato, Masashi (Frontiers in Behavioral Neuroscience, 2017)
General electric devices and ventilation systems are known to generate low frequency noise (LFN) with frequencies of less than 100 Hz. Previous studies showed that exposure to LFN caused impairments of balance in humans and mice during adulthood. On the other hand, a previous study showed that noise levels in the neonatal intensive care unit (NICU) were greater than those in general home or office environments. Therefore, it is possible that neonates have a potential risk to be exposed to LFN in the NICU. However, the risk of neonatal exposure to LFN remains unclear in humans and mice. In this study, male ICR mice were exposed to LFN at 100 Hz for 4 weeks after birth and then subjected to rotarod and beam crossing tests in order to assess LFN-mediated risk of imbalance during the neonatal period. Exposure to LFN at 70 dB, but not exposure to LFN up to 60 dB, during the neonatal period significantly decreased performance scores for rotarod and beam crossing tests compared to the scores of the control group. The number of calbindin-positive hair cells in the saccule and utricle was decreased in mice exposed to LFN at 70 dB for 4 weeks in the neonatal phase. Cessation of exposure for 10 weeks did not result in recovery of the decreased performance in rotarod and beam crossing tests. Thus, our results suggest that 70 dB is a possible threshold for exposure to LFN for 4 weeks during the neonatal period causing unrecoverable imbalance in mice.